Resin for UV photocuring intrinsic antifouling paint and preparation method thereof

A UV light-curable antifouling coating resin using elemental sulfur and diacrylate monomers addresses slow curing and photoinitiator requirements, achieving rapid curing and antibacterial properties without photoinitiators.

CN119219854APending Publication Date: 2024-12-31CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411489969.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing marine antifouling coatings are thermally cured, with slow curing rates and low efficiency, and often require photoinitiators, lacking antifouling properties.

Method used

A UV light-curable intrinsic antifouling coating resin is prepared by mixing elemental sulfur, glycidyl methacrylate, and diacrylate monomers, catalyzed by alkaline catalysts, which generates free radicals under UV irradiation for room temperature curing without photoinitiators, using reactive diluents for viscosity reduction and incorporating sulfur for antibacterial and self-polishing properties.

Benefits of technology

The UV curing process achieves rapid curing in 10-40 seconds, eliminates the need for photoinitiators, and provides coatings with antibacterial and self-polishing properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219854A_ABST
    Figure CN119219854A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of marine antifouling paint, and particularly relates to resin for UV photocuring intrinsic antifouling paint and a preparation method of the resin. The raw materials for preparing the resin comprise elemental sulfur, glycidyl methacrylate and a diacrylate monomer, the reactive diluent is isoamyl methacrylate, methacrylic acid or styrene, and the reaction temperature is 25-60 DEG C. The introduction of elemental sulfur and a binary acrylate monomer endows the coating with antibacterial and antifouling properties. The use of the reactive diluent not only can effectively reduce the viscosity of the reaction system, but also has no TOC emission. The curing mode adopted for preparing the antifouling paint is ultraviolet light room temperature curing, and the antifouling paint has the advantages of being high in curing speed and efficiency and not needing to additionally introduce a photoinitiator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of marine antifouling coatings, and in particular relates to a resin for UV light-curing intrinsic antifouling coatings and a preparation method thereof. Background Art

[0002] Marine biofouling affects the development of the marine industry, and the development of marine antifouling coatings can effectively solve this problem. In recent years, with the development of environmentally friendly antifouling coatings, such as organotin antifouling coatings and antifouling coatings containing cuprous oxide have been discontinued. Typical environmentally friendly antifouling coatings include low surface energy antifouling coatings and biodegradable antifouling coatings. For biodegradable antifouling coatings, combining environmentally friendly antifouling agents with them will have better antifouling effects. Ultraviolet light curing technology has the advantages of environmental protection, safety, high efficiency and energy saving, and can be applied to the preparation of marine antifouling coatings. However, existing marine antifouling coatings are generally thermally cured, with slow curing rate and low efficiency, and the coatings often need to add photoinitiators during light curing.

[0003] CN 103525264 A, a UV curing UV coating and a preparation method thereof, is prepared from the following raw materials in parts by weight: 50-60 of epoxy acrylate, 20-25 of methacrylate, 6-8 of 2-hydroxy-2-methyl-propiophenone, 10-12 of dimethylaminoethyl methacrylate, 1-2 of polyoxyethylene stearate, 10-12 of dipentaerythritol hexaacrylate, 3-5 of ethylene glycol ethyl ether acetate, 1-2 of silane coupling agent KH-550, 3-4 of accelerator DM, 2-3 of acrylic acid-4-2, 1-2 of glycidyl methacrylate, 2-3 of ditetradecyl alcohol ester, 1-2 of antioxidant DSTP, and 4-5 of dispersing aid. The preparation of the coating in this patent requires the use of a photoinitiator 2-hydroxy-2-methyl-propiophenone, and the synthesized coating does not have antifouling properties. Summary of the invention

[0004] In order to solve the technical problems existing in the background technology, the present invention provides a UV light-curable intrinsic antifouling coating resin, and the preparation method thereof is as follows: a certain proportion of elemental sulfur, glycidyl methacrylate, diacrylate monomer and reactive diluent are mixed, and then a step reaction is carried out under the catalysis of an alkaline catalyst to obtain a room temperature UV light-curable intrinsic antifouling coating resin.

[0005] The molar ratio of glycidyl methacrylate to the dibasic acrylate monomer is (1-2):1, and the molar ratio of elemental sulfur to the dibasic acrylate monomer is (0.5-0.75):1.

[0006] The diacrylate monomers are 1,6-hexanediol diacrylate, polycaprolactone diacrylate, tripropylene glycol diacrylate, and pentaerythritol diacrylate. Among them, polycaprolactone diacrylate contains a large number of ester bonds and is easily degraded in large quantities, tripropylene glycol diacrylate can improve the hardness and durability of the coating, and pentaerythritol diacrylate can improve the adhesion and chemical resistance of the coating.

[0007] The reactive diluent is a commonly used vinyl monomer such as isoamyl methacrylate, methacrylate or styrene.

[0008] The basic catalyst is 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD), 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD).

[0009] The specific preparation method of the UV light-curing intrinsic antifouling coating resin is as follows: in an inert gas atmosphere, elemental sulfur, glycidyl methacrylate, and diacrylate monomer are added to a flask, and an active diluent is added and stirred for 1 minute. Then, an alkaline catalyst is added, and the reaction is carried out at 25-60° C. for 24-48 hours to obtain a UV light-curing intrinsic antifouling coating resin.

[0010] The UV light curing process is: a certain amount of antifouling coating resin is evenly applied on the epoxy board, and UV curing is carried out at room temperature. The UV wavelength is 315nm-400nm and the curing time is 10-40s.

[0011] Compared with the prior art, the present invention has the following advantages and technical effects:

[0012] 1. The curing method used in the present invention is ultraviolet light curing at room temperature, which has a shorter curing time, only 10-40 seconds to complete, thus simplifying the time required for preparing the coating.

[0013] 2. The UV curing used in the present invention does not require a photoinitiator, because the SS bonds in the degradable sulfur-containing polymer can automatically generate free radicals under UV irradiation, which breaks through the condition that conventional UV curing requires a photoinitiator.

[0014] 3. The reactive diluent used in the present invention can not only reduce the viscosity of the reaction system, but also has no TOC emission; the elemental sulfur and dibasic acrylate monomers used give the coating good antibacterial properties and self-polishing properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 1 is the H NMR spectrum of the antifouling coating resin prepared in Example 1.

[0016] Figure 2 It is the GPC chart of the antifouling coating resin of Examples 1, 2, and 6.

[0017] Figure 3 These are images of the sedimentation of Phaeodactylum tricornutum on the coating surfaces prepared in Examples 2, 6, and 7 for 30 days (1, 2, 3) and a control group (4, epoxy resin board).

[0018] Figure 4 These are images of the coatings prepared in Examples 2, 6, and 8 hung on Xiamen boards for 6 months (1, 2, and 3) and a control group (4, epoxy resin board). DETAILED DESCRIPTION

[0019] In order to make the researchers in this field more clearly understand the purpose, technical solutions and advantages of the present invention, the present invention is further described below in conjunction with specific examples. The specific examples described are only used to explain the present invention and are not used to limit the present invention.

[0020] Example 1

[0021] Under an inert gas atmosphere, a mixture of 1.9239 g (0.0075 mol) of elemental sulfur, 10 g (0.01 mol) of polycaprolactone diacrylate (relative molecular weight of about 1000 g / mol), and 1.4215 g (0.01 mol) of glycidyl methacrylate was added to a 50 mL small flask, and then 5.28 mL (0.03 mol) of isoamyl methacrylate was added to dissolve, and the mixture was stirred on a magnetic stirrer for about 1 min, and 0.0152 g (0.0001 mol) of 1,8-diazabicyclo[5.4.0]undec-7-ene was added to the flask. The mixture was reacted in an oil bath at 30 ° C for 24 hours, and the reaction was terminated to obtain a resin solution. Finally, the resin solution was scraped onto an epoxy board and cured by ultraviolet light at room temperature for 20 seconds to obtain the UV light-cured intrinsic antifouling coating.

[0022] Example 2

[0023] Under an inert gas atmosphere, a mixture of 1.2826g (0.005mol) of elemental sulfur, 10g (0.01mol) of polycaprolactone diacrylate (relative molecular weight of about 1000g / mol), and 1.4215g (0.01mol) of glycidyl methacrylate was added to a 50mL small flask, and then 5.28mL (0.03mol) of isoamyl methacrylate was added to dissolve, and the mixture was stirred on a magnetic stirrer for about 1min, and 0.0152g (0.0001mol) of 1,8-diazabicyclo[5.4.0]undec-7-ene was added to the flask. The mixture was reacted for 36 hours in an oil bath at 30°C, and the reaction was terminated to obtain a resin solution. Finally, the resin solution was scraped onto an epoxy board and cured by ultraviolet light at room temperature for 20s to obtain the UV light-cured intrinsic antifouling coating.

[0024] Example 3

[0025] Under an inert gas atmosphere, a mixture of 1.9239 g (0.0075 mol) of elemental sulfur, 10 g (0.01 mol) of polycaprolactone diacrylate (relative molecular weight of about 1000 g / mol), and 2.843 g (0.02 mol) of glycidyl methacrylate was added to a 50 mL small flask, and then 5.28 mL (0.03 mol) of isoamyl methacrylate was added to dissolve, and the mixture was stirred on a magnetic stirrer for about 1 min, and 0.0152 g (0.0001 mol) of 1,8-diazabicyclo[5.4.0]undec-7-ene was added to the flask. The mixture was reacted in an oil bath at 30 ° C for 48 hours, and the reaction was terminated to obtain a resin solution. Finally, the resin solution was scraped onto an epoxy board and cured by ultraviolet light at room temperature for 20 seconds to obtain the UV light-cured intrinsic antifouling coating.

[0026] Example 4

[0027] Under an inert gas atmosphere, a mixture of 1.9239 g (0.0075 mol) of elemental sulfur, 10 g (0.01 mol) of polycaprolactone diacrylate (relative molecular weight of about 1000 g / mol), and 2.843 g (0.02 mol) of glycidyl methacrylate was added to a 50 mL small flask, and then 5.28 mL (0.03 mol) of isoamyl methacrylate was added to dissolve, and the mixture was stirred on a magnetic stirrer for about 1 min, and 0.0153 g (0.0001 mol) of 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene was added to the flask. The mixture was reacted for 24 hours in an oil bath at 30 ° C, and the reaction was terminated to obtain a resin solution. Finally, the resin solution was scraped onto an epoxy board and cured by ultraviolet light at room temperature for 20 seconds to obtain the UV light-cured intrinsic antifouling coating.

[0028] Example 5

[0029] Under an inert gas atmosphere, a mixture of 1.9239 g (0.0075 mol) of elemental sulfur, 10 g (0.01 mol) of polycaprolactone diacrylate (relative molecular weight of about 1000 g / mol), and 2.1323 g (0.015 mol) of glycidyl methacrylate was added to a 50 mL small flask, and then 5.28 mL (0.03 mol) of isoamyl methacrylate was added to dissolve, and the mixture was stirred on a magnetic stirrer for about 1 min, and 0.0152 g (0.0001 mol) of 1,8-diazabicyclo[5.4.0]undec-7-ene was added to the flask. The mixture was reacted for 36 hours in an oil bath at 30 ° C, and the reaction was terminated to obtain a resin solution. Finally, the resin solution was scraped onto an epoxy board and cured by ultraviolet light at room temperature for 20 seconds to obtain the UV light-cured intrinsic antifouling coating.

[0030] Example 6

[0031] Same as Example 1, except that the amount of elemental sulfur added is 1.6033 g (0.00625 mol).

[0032] Example 7

[0033] The same as Example 1, except that the organic base catalyst is 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and the added amount is 0.0139 g (0.0001 mol).

[0034] Example 8

[0035] The same as Example 1, except that the organic base catalyst is 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, and the added amount is 0.0153 g (0.0001 mol).

[0036] Example 9

[0037] The same as Example 1, except that the diacrylate monomer is 1,6-hexanediol diacrylate, and the added amount is 2.24 mL (0.01 mol).

[0038] Example 10

[0039] The same as Example 1, except that the diacrylate monomer is tripropylene glycol diacrylate, and the added amount is 3.0035 g (0.01 mol).

[0040] Embodiment 11

[0041] The same as Example 1, except that the diacrylate monomer is pentaerythritol diacrylate, and the added amount is 2.4424 g (0.01 mol).

[0042] Example 12

[0043] Same as Example 1, except that the reactive diluent is methacrylic acid.

[0044] Example 13

[0045] Same as Example 1, except that the reactive diluent is styrene.

[0046] The structure of the antifouling coating resin (prepared in Example 1) was characterized by nuclear magnetic hydrogen spectrum using a Swiss Bruker-ARX-400 nuclear magnetic resonance spectrometer. The deuterated reagent used was deuterated dimethyl sulfoxide, the internal standard was tetramethylsilane (TMS), the resolution was <0.2 Hz, the sensitivity was >100, the magnetic field strength was 7.05 T, the test was performed at room temperature, the number of scans was 32 times, and the results were as follows: Figure 1 , Figure 1 In the figure, the peak with a chemical shift near 6 ppm corresponds to the characteristic absorption peak of the double bond, indicating that the carbon-carbon double bond in glycidyl methacrylate has not reacted and can be used for the curing reaction.

[0047] The molecular weight of the antifouling coating resin was characterized by a three-detection gel permeation chromatograph (GPC) from Waters, USA. The test temperature was 35°C, linear PMMA was used as the standard sample, THF was used as the mobile phase, and the test flow rate was 1.0 mL min -1 The chromatographic separation columns are StyagelHR1THF 7.8×300mm, StyagelHR3THF 7.8×300mm, StyagelHR4THF 7.8×300mm and StyagelHR5THF 7.8×300mm, which are connected in series. The results are as follows Figure 2 , Figure 2 This is a graph of the molecular weight of antifouling coating resins at different sulfur contents. It can be seen that as the amount of elemental sulfur added continues to decrease, the weight-average molecular weight of the polymer decreases accordingly.

[0048] Anti-diatom adhesion performance test: A 2.5 mm × 7.5 mm coating (resin prepared in Examples 2, 6, and 7) was fixed in a culture dish containing a solution of P. triangularis. After standing for 30 days, the algae solution was taken out and immersed in sterile ASW. The diatoms were then fixed with 2.5% glutaraldehyde. After that, the diatoms were rinsed with sterile ASW and dried naturally. The results were observed under a fluorescence microscope. Figure 3 ,Depend on Figure 3It can be seen that after 30 days of sedimentation, the surface of the epoxy resin board alone was covered with a large amount of P. triangularis, while the surface of the coating of the present invention had almost no P. triangularis attached, and with the increase of sulfur content, the amount of P. triangularis attached gradually decreased, indicating that the coating has good anti-diatom attachment ability.

[0049] Ocean hanging board test: The ocean hanging board test was carried out in Xiamen Bay. The sample (resin prepared in Examples 2, 6, and 8) was coated on an epoxy board, and then the fixed test raft was lowered into the sea water at a depth of 0.2 to 2 meters. After a period of time, the board was taken out of the sea water, carefully rinsed with sea water, and photographed. The results are as follows: Figure 4 ,Depend on Figure 4 It can be seen that, similarly, after hanging the boards in Xiamen for 6 months, the surface of the epoxy resin board alone was covered with a large number of fouling organisms, while the surface of the coating of the present invention had almost no fouling organisms attached, and as the sulfur content increased, the amount of fouling organisms attached gradually decreased, indicating that the coating has a good anti-fouling effect.

[0050] Table 1 Performance comparison of different diacrylate monomer coatings

[0051] Quality loss rate (% / 30 days) Hardness (HB) Adhesion(MPa) Example 1 45 2 22 Example 9 12 2 18 Example 10 10 6 20 Embodiment 11 7 3 26

[0052] The above embodiments are only preferred implementation schemes of the present invention. The present invention can still be implemented in other forms. Any similar replacement schemes used by technicians familiar with the profession are within the protection scope of the present invention.

Claims

1. A UV light-curable resin for intrinsic antifouling coating, characterized in that: The resin is obtained by reacting elemental sulfur, glycidyl methacrylate and diacrylate in a reactive diluent under the catalysis of an alkaline catalyst.

2. The UV light-curable intrinsic antifouling coating resin according to claim 1, characterized in that: The molar ratio of glycidyl methacrylate to dibasic acrylate is 1-2:1, and the molar ratio of elemental sulfur to dibasic acrylate is 0.5-0.75:

1.

3. The UV light-curable intrinsic antifouling coating resin according to claim 1, characterized in that: The dibasic acrylate is 1,6-hexanediol diacrylate, polycaprolactone diacrylate, tripropylene glycol diacrylate, and pentaerythritol diacrylate.

4. The UV light-curable intrinsic antifouling coating resin according to claim 1, characterized in that: The reactive diluent is isoamyl methacrylate, methacrylate or styrene.

5. The UV light-curable intrinsic antifouling coating resin according to claim 1, characterized in that: The reaction temperature is 25-60° C., and the reaction time is 24-48 hours.

6. A method for preparing a UV light-curable intrinsic antifouling coating resin according to claim 1, characterized in that: The preparation method of the resin comprises the following steps: adding elemental sulfur, glycidyl methacrylate and diacrylate into a flask under an inert gas atmosphere, adding an active diluent and stirring for 1 minute; and then adding an alkaline catalyst for reaction to obtain a UV light-cured intrinsic antifouling coating resin.

7. A method for applying the UV light-curable intrinsic antifouling coating resin according to claim 1, characterized in that: The process of UV light curing of the resin for intrinsic antifouling coating is: the resin for antifouling coating is evenly coated on the epoxy board and UV cured at room temperature.

8. The use of the UV light-curable intrinsic antifouling coating resin according to claim 7, characterized in that: The UV wavelength is 315nm-400nm, and the curing time is 10-40s.